2006
DOI: 10.2495/su060411
|View full text |Cite
|
Sign up to set email alerts
|

Energy absorption of safety nets in building construction

Abstract: Safety nets used in buildings under construction in Europe are examples of structures under impact. It would be of great interest to evaluate the energy absorbed by the elements making up these devices (nets and supports) in order to improve them and quantify injuries to victims of falls. Experimental tests on type "V" safety nets (EN 1263-1, 1997) were numerically modelled in this work (consisting of dropping a 100 kg weight from 7 m above the nets). The model is dynamic and highly non-linear (variable contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…The existing flexible protection system generally uses nylon net [40], which is formed by crossing high-strength nylon ropes and can be connected to the building through support ropes and covered on the holes of the building structure to provide protection, as shown in Figure 1. Research [23,24] has shown that almost all impact energy of such protective systems is dissipated by the large deformation of the protective mesh when subjected to impact. Due to its simple structure and the poor energy consumption capacity of nylon rope nets, the protective capacity of the protective system cannot exceed 30 kJ.…”
Section: Existing Protection Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing flexible protection system generally uses nylon net [40], which is formed by crossing high-strength nylon ropes and can be connected to the building through support ropes and covered on the holes of the building structure to provide protection, as shown in Figure 1. Research [23,24] has shown that almost all impact energy of such protective systems is dissipated by the large deformation of the protective mesh when subjected to impact. Due to its simple structure and the poor energy consumption capacity of nylon rope nets, the protective capacity of the protective system cannot exceed 30 kJ.…”
Section: Existing Protection Systemmentioning
confidence: 99%
“…Filho [22] compared two fall protection measures used in construction in Brazil and found that protective measures with safety nets are safer. Segovia [23] established a numerical model to simulate the impact test of a "V"-type safety net with an impact energy of 7 kJ, emphasizing the importance of energy absorption. Chen [24] studied the protective performance of high-strength nylon nets.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively it can be predicted using numerical models [12,13]. Table 3 shows the deflection value in each safety system, along with the corresponding energies and maximum accelerations (and forces), as predicted by numerical models.…”
Section: Measurementmentioning
confidence: 99%
“…Moreover, the lack of information, together with the findings from recent detailed studies point to the fact that some of these values are questionable or even inadequate [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%